2003
DOI: 10.1046/j.1469-0691.2003.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Mueller–Hinton agar is superior to PDM blood agar for detection of methicillin-resistant Staphylococcus aureus

Abstract: The aim of this study was to compare the expression of oxacillin resistance in methicillin-resistant Staphylococcus aureus (MRSA) on Paper Disc Method agar supplemented with 5% defibrinated blood (PDM blood agar) and Mueller-Hinton agar supplemented with 2% NaCl (MH NaCl agar) using different susceptibility tests. Fifty mecA-containing isolates of S. aureus, exhibiting 46 different pulsed-field gel electrophoresis patterns, were comparatively tested using the E test, the single disk diffusion test, and the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…13 CNS are associated with bacteremia, wound-related infections, intravascular catheter-related infections, and a variety of postoperative infections. 14 Moreover, it has been shown that CNS have the ability to develop resistance to all hitherto described antibiotics and multidrug-resistant CNS are currently a common finding among hospitalized patients. 46 The emergence of multidrug-resistant CNS has limited the therapeutic arsenal, thus increasing the risk of treatment failure and costs.…”
mentioning
confidence: 99%
“…13 CNS are associated with bacteremia, wound-related infections, intravascular catheter-related infections, and a variety of postoperative infections. 14 Moreover, it has been shown that CNS have the ability to develop resistance to all hitherto described antibiotics and multidrug-resistant CNS are currently a common finding among hospitalized patients. 46 The emergence of multidrug-resistant CNS has limited the therapeutic arsenal, thus increasing the risk of treatment failure and costs.…”
mentioning
confidence: 99%
“…To confirm the MRSA strains, Mueller Hinton agar plates containing 4% NaCl were inoculated and incubated at 35 and 42°C for 24 hours. The bacterial inhibition halos of the bacterial growth on the agar plates were expressed in mm and compared to the established values for the test with a difference >4 mm in diameter between the halos of inhibition containing unidisks with 1, 2, 4, and 6 μg of oxacicline [31]. The in vitro production of β-lactamase was determined by the modified iodometric method [32].…”
Section: Staphylococcus Aureus Methicillin-resistant Strains Identifimentioning
confidence: 99%
“…In 1990, a study noted that the mecA gene was not found in methicillin-susceptible isolates of staphylococci (Archer & Pennell, 1990;Louie et al, 2000a). However, later a study demonstrated that the mecA gene was regarded as the benchmark for identifying methicillin-resistant Staphylococcus aureus (MRSA) (Monsen et al, 2003;Unal et al, 1994b). Further studies reported that MRSA strains bearing the genes encoding for Panton-Valentine leucocidin (PVL), a highly powerful toxin, have been accountable for a serious threat to public health (Holmes et al, 2005;Sina et al, 2018).…”
Section: Introductionmentioning
confidence: 99%